Asservimento e liberazione. Nietzsche e la consacrazione della cultura - Giaculli, Fiorella (Mechane, 2025)
This article aims to outline Nietzsche’s conception of culture as developed during his early “Basel years”, with particular attention to his critical engagement with the cultural landscape of his time. It further proposes that Nietzsche’s perspective may offer a hermeneutic key for rethinking and defending the meaning and function of culture even today.